2011
DOI: 10.1096/fj.11-184556
|View full text |Cite
|
Sign up to set email alerts
|

Antigen depot is not required for alum adjuvanticity

Abstract: Alum adjuvants have been in continuous clinical use for more than 80 yr. While the prevailing theory has been that depot formation and the associated slow release of antigen and/or inflammation are responsible for alum enhancement of antigen presentation and subsequent T- and B-cell responses, this has never been formally proven. To examine antigen persistence, we used the chimeric fluorescent protein EαGFP, which allows assessment of antigen presentation in situ, using the Y-Ae antibody. We demonstrate that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 34 publications
10
158
1
6
Order By: Relevance
“…This observation reinforces that a short period of local sterile inflammation is enough to "educate" DCs in bridging an innate to adaptive immune response as we previously demonstrated (5). This important notion is strongly supported by the investigation showing that surgical removal of the inoculation site containing alum 2 h after vaccination did not compromise the adjuvant effect of alum (26). The study, along with our observations, argues strongly the dispensability of prolonged inflammation at the inoculation site for effective vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation reinforces that a short period of local sterile inflammation is enough to "educate" DCs in bridging an innate to adaptive immune response as we previously demonstrated (5). This important notion is strongly supported by the investigation showing that surgical removal of the inoculation site containing alum 2 h after vaccination did not compromise the adjuvant effect of alum (26). The study, along with our observations, argues strongly the dispensability of prolonged inflammation at the inoculation site for effective vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…All experiments were repeated twice with similar results. inoculation site was not necessary for effective immunization (5,26). Moreover, in comparison with vaccination of MNs alone, NAFL treatment significantly enhanced the immune responses, without incurring any adverse events.…”
Section: Nafl Significantly Broadens Immunity Induced By Influenza Vamentioning
confidence: 93%
“…Alum appears to form a depot with some antigens (12) but not others (115) and likely undergoes desorption of some antigens under in vivo conditions (116). Recent studies have further demonstrated that, following alum immunization, the injection site can be surgically removed 2 hours after injection with no effect on the humoral immune response, suggesting that depot formation is not a critical part of alum's mechanism of action (117,118).…”
Section: Programming Vaccine Kineticsmentioning
confidence: 99%
“…Hutchison et al demonstrated that removing the injection site 2 h after immunization did not result in compromised immune responses, indicating that the antigen deposit e®ect may not be important for the adjuvant e®ect of Alum. 30 Meanwhile, a number of studies suggested the underlying mechanism owing to toxicity of Alum 31 : Alum kills host cells, and dead cells in turn release danger signals, including uric acid, genomic DNAs, etc. [31][32][33] These danger signals are designated as damage-associated molecular patterns (DAMPs).…”
Section: Laser Induced Micro-sterile In°ammation Array As Vaccine Adjmentioning
confidence: 99%